'Things Fall Apart': a story of leadership, intuition, and social transformation - Gosling, Jonathan (Henry Stewart Talks, 2019)
This case study critiques the character of Okonkwo from the novel Things Fall Apart by Chinua Achebe and analyses his leadership style.